Sex-Related Differences in Long-Term Outcomes After Early-Onset Myocardial Infarction - Ardissino, Maddalena; Nelson, Adam J.; Maglietta, Giuseppe; Malagoli Tagliazucchi, Guidantonio; Disisto, Caterina; Celli, Patrizia; Ferrario, Maurizio; Canosi, Umberto; Cernetti, Carlo; Negri, Francesco; Merlini, Piera Angelica; Tubaro, Marco; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: There is growing awareness of sex-related differences in cardiovascular risk profiles, but less is known about whether these extend to pre-menopausal females experiencing an early-onset myocardial infarction (MI), who may benefit from the protective effects of estrogen exposure. Methods: A nationwide study involving 125 Italian Coronary Care Units recruited 2,000 patients between 1998 and 2002 hospitalised for a type I myocardial infarction before the age of 45 years (male, n = 1778 (88.9%). Patients were followed up for a median of 19.9 years (IQR 18.1-22.6). The primary composite endpoint was the occurrence of cardiovascular death, non-fatal myocardial re-infarction or non-fatal stroke, and the secondary endpoint of hospitalisation for revascularisation by means of a percutaneous coronary intervention (PCI) or coronary artery bypass surgery (CABG). Results: ST-elevation MI was the most frequent presentation among both men and women (85.1 vs 87.4%, p=ns), but the men had a greater baseline coronary atherosclerotic burden (median Duke Coronary Artery Disease Index: 48 vs 23; median Syntax score 9 vs 7; both p<0.001). The primary composite endpoint occurred less frequently among women (25.7% vs 37.0%; adjusted hazard ratio: 0.69, 95% CI 0.52-0.91; p=0.01) despite being less likely to receive treatment with most secondary prevention medications during follow up. Conclusions: There are significant sex-related differences in baseline risk factors and outcomes among patients with early-onset MI: women present with a lower atherosclerotic disease burden and, although they are less frequently prescribed secondary prevention measures, experience better long-term outcomes.